2009
DOI: 10.1007/s12024-009-9126-4
|View full text |Cite
|
Sign up to set email alerts
|

Repeated or long-duration TASER® electronic control device exposures: acidemia and lack of respiration

Abstract: Conducted energy weapons (CEWs), such as TASER devices, may be applied to subjects in repeated or long-duration modes. Such applications may result in more potentially harmful effects (as reflected in blood factor changes) than shorter exposures. In this review, results from a number of studies of repeated and long-duration CEW exposures in an animal model are examined. Additionally, a few limited investigations of shorter CEW applications to human subjects are considered. Specifically, in anesthetized swine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Reviews on this topic however are worryingly uncommon -only two studies in the past twelve years [71,72]. None, to our knowledge, have been performed for the forensic scenario.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reviews on this topic however are worryingly uncommon -only two studies in the past twelve years [71,72]. None, to our knowledge, have been performed for the forensic scenario.…”
Section: Discussionmentioning
confidence: 97%
“…From this point of view, the history of forensic sciences has provided us with much evidence of the inapplicability of data obtained from studies performed on animal models, including the Daubert sentence [66] and several recent studies have again stressed the limits of this approach in different fields of forensic sciences, from the estimation of post mortem interval to genetics [67][68][69][70][71][72][73][74][75]. In an article concerning the effectiveness of triphenyltetrazolium chloride to detect acute myocardial infarction, the authors state that "it is not realistic to apply methods confirmed in animals" [68].…”
Section: Discussionmentioning
confidence: 99%
“…While this was clinically not important for the duration studied, it could perhaps have implications for longer durations. In a review by Jauchem, he noted that animal studies have shown impaired respiration and prolonged exposures had caused a mixed metabolic and respiratory acidosis [11]. Although in his review, the durations of exposure where longer than would be expected in field use.…”
Section: Discussionmentioning
confidence: 99%
“…The study found no statistical difference between the TASER exposure and the additional brief exertion in the groups that had the initial exertion regimen. In the previously mentioned review by Jauchem, it was noted that animal studies with prolonged durations have shown significant evidence of metabolic acidosis with lactates to 24 mmol/L after 18 repeated 7-s exposures [11].…”
Section: Discussionmentioning
confidence: 99%
“…Even though some animal studies point out certain potential risk factors after an exposure to CEWs, such as increased hematocrit, acidosis or lack of effective respiration [9][10][11][12][13], these Conducted electrical weapons (CEWs) deliver short high-voltage, low current energy pulses to temporarily paralyze a person by causing muscular contraction.…”
mentioning
confidence: 99%